Transparent bamboo building material with high strength, high toughness and adjustable photo-thermal performance and preparation method of transparent bamboo building material
By using alkaline sodium sulfite anthraquinone methanol reagent to treat bamboo under high temperature and high pressure conditions, combined with chlorine dioxide solution and mechanical pressure forming technology, the problems of long process time and high energy consumption in the existing transparent bamboo preparation methods are solved, and transparent bamboo preparation with high strength and high toughness and adjustable photothermal performance is achieved. The material can naturally degrade, retaining green and environmentally friendly properties.
Patent Information
- Application Number
- CN202510006907.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-02-28
Smart Images

Figure CN119526531A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a transparent bamboo building material with high strength and toughness and adjustable light and heat properties, and a preparation method thereof. Background Art
[0002] The latest statistics from the United Nations Environment Programme in 2024 show that energy consumption throughout the construction industry has become the main source of global energy consumption and greenhouse gas emissions. This is because traditional building materials, such as concrete, steel, masonry and other structural building materials, not only consume a lot of energy in the early production process, but also in the subsequent use process, due to low light transmittance and poor thermal insulation performance, resulting in insufficient indoor lighting and difficulty in temperature control, which significantly increases the lighting energy consumption and air-conditioning load during the building operation stage. Although transparent building materials represented by glass can effectively use natural light for lighting and temperature control, they also have high thermal conductivity (1.2-1.34W / (m . K)), poor thermal insulation performance and other issues have seriously affected the energy efficiency of buildings. Therefore, the use of green and environmentally friendly renewable raw materials to prepare low-carbon and energy-saving transparent building materials has important practical significance for promoting energy conservation and emission reduction in the construction field.
[0003] Bamboo is a renewable resource with abundant reserves, wide distribution, short growth cycle and low thermal conductivity (0.3-0.4W / (m .K)), and has good mechanical properties and environmental durability, and is widely used in the construction field. However, as a natural material, bamboo contains a high mass proportion of lignin (21%-34%) in its cells, in addition to cellulose and hemicellulose components that do not absorb visible light. Due to the strong light absorption performance of lignin (accounting for 80%-95% of the light absorbed by bamboo), the light transmittance of bamboo is low. At the same time, there are multi-level pore structures of different sizes in the tissues such as ducts, fibers and thin-walled cells inside the bamboo, and the porosity distribution range is 48%-70%, which causes light to scatter when passing through the bamboo, seriously affecting the light transmittance. Most of the existing papers and patents on the preparation of transparent bamboo reduce light absorption by removing lignin, and fill the pores to reduce light scattering by impregnating polymers with the same refractive index as cellulose (papers: ACS Appl. Mater. Interfaces., 2020, 13 (1): 1662; Chem. Eng. J., 2023, 451: 138349; Int. J. Biol. Macromol., 2024, 277: 134470; patents: CN110978183B; CN113664938B; CN114851323B; CN117124426A). However, bamboo has a dense structure and uneven lignin distribution. The delignification process reported in the above papers and patents takes a long time, consumes a lot of chemicals, consumes a lot of energy, and has low efficiency. In addition, the composite materials formed by impregnation with polymers such as epoxy resin and acrylate are difficult to degrade naturally, which weakens the inherent low-carbon and green properties of bamboo. Therefore, there is an urgent need to develop a new method that is simple, efficient, energy-saving and environmentally friendly to prepare transparent bamboo building materials with adjustable light and heat management capabilities and that can be naturally degraded at the end of their life. Summary of the invention
[0004] The purpose of the present invention is to propose a transparent bamboo building material with high strength and toughness and adjustable light and heat properties and a preparation method thereof, which can be used not only for windows and skylights of buildings, but also for interior decoration, indoor partitions, etc., by effectively adjusting the transmittance of solar radiation, reducing indoor temperature fluctuations, and reducing the energy consumption of air conditioning and lighting, thereby making a greater contribution to building energy conservation and sustainable development.
[0005] The technical solution of the present invention is achieved in this way:
[0006] The present invention provides a method for preparing a transparent bamboo building material with high strength, high toughness and adjustable light and heat properties, comprising the following steps:
[0007] (1) Flattened bamboo board is used as raw material, and a mixed reagent of alkaline sodium sulfite anthraquinone methanol is selected as a medium for softening and swelling bamboo tissue and depolymerizing and dissolving lignin. After being placed in a high-pressure reactor for high-temperature treatment for a period of time, it is washed with clean water to quickly and evenly dissolve most of the lignin while keeping the flattened bamboo morphology and structure intact;
[0008] (2) transferring the bamboo board from which a large amount of lignin has been removed to a chlorine dioxide solution for treatment for a period of time to further selectively remove and dissolve the residual lignin;
[0009] (3) The bamboo board from which all lignin has been removed is washed with clean water, transferred to a mold of a constant temperature pressure molding equipment, and subjected to low temperature pressing treatment to obtain a transparent bamboo board.
[0010] As a further improvement of the present invention, the flattened bamboo board in step (1) is derived from three to five-year-old moso bamboo, bamboo stalk or giant dragon bamboo, and the density of the flattened bamboo board is 0.5-0.8 g / cm 3 .
[0011] Preferably, the flattened bamboo board has a size of 40-200 cm in length, 20-60 cm in width, and 0.2-2 cm in thickness.
[0012] As a further improvement of the present invention, the initial cellulose content in the flattened bamboo board in step (1) is 30%-35%, the initial degree of polymerization DP value of cellulose is 1500-2500, the initial hemicellulose content is 20%-25%, and the initial lignin content is 21%-35%.
[0013] As a further improvement of the present invention, in the alkaline sodium sulfite anthraquinone methanol mixed reagent in step (1), the mass ratio of alkali, sodium sulfite, methanol and anthraquinone to distilled water is 0.01-0.1:0.1-0.2:0.1-0.2:0.001-0.005:1; the alkali is selected from at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide; and the mass ratio of the flattened bamboo material to the alkaline sodium sulfite anthraquinone methanol mixed reagent is 1:5-10.
[0014] As a further improvement of the present invention, the reaction temperature of the high temperature treatment in step (1) is 120-180° C., the pressure value is 0.15-1.2 MPa, and the treatment time is 0.5-6 h.
[0015] As a further improvement of the present invention, the lignin content of the bamboo board treated in step (1) is reduced to 2%-10%, the hardness is reduced to 300-1200 Pa, and the degree of polymerization DP value of cellulose is 1000-1500.
[0016] As a further improvement of the present invention, the effective chlorine content of the chlorine dioxide solution in step (2) is 8%-20%, the mass ratio of the bamboo board treated in step (1) to the chlorine dioxide solution is 1:10-20, the treatment temperature is 40-90°C, and the treatment time is 0.5-12h.
[0017] As a further improvement of the present invention, the lignin mass of the bamboo board treated in step (2) is reduced to less than 0.5%, and the degree of polymerization DP value of cellulose is 980-1400.
[0018] As a further improvement of the present invention, the mechanical pressure molding equipment in step (3) refers to a constant temperature hot press or a flat vulcanizer, the molding mold is a flat metal plate or metal frame, and the unit pressure is 0.1-10MPa / m 2 The processing temperature of the low-temperature pressing treatment is 25-40°C, and the pressure treatment time is 0.1-24h.
[0019] As a further improvement of the present invention, during the low-temperature pressing process in step (3), a blanket made of nylon, polypropylene, polyester or cotton yarn is selected to cover and cushion the delignified bamboo board and absorb and remove water.
[0020] The present invention further protects a transparent bamboo building material with high strength, high toughness and adjustable light and heat properties obtained by the above-mentioned preparation method, wherein the density of the transparent bamboo building material is 1.0-1.5 g / cm 3 , the moisture content is 5%-10%, the optical transmittance and haze range are 40%-90% and 20%-80% respectively, and the thermal conductivity is 0.2-0.6W / (m . K), tensile strength of 500-1000MPa, and flexural strength of 300-700MPa.
[0021] As a further improvement of the present invention, by coating the surface of the transparent bamboo with hydrophobic substances such as polylactic acid, nylon, paraffin, silicone-fluorine compounds, or spraying with photochromic nanoparticles such as vanadium dioxide and metal-organic frameworks, the long-term stable service performance and light and heat management performance of the transparent bamboo are improved.
[0022] The present invention has the following beneficial effects:
[0023] Bamboo is treated with alkaline sodium sulfite anthraquinone methanol reagent under high temperature and high pressure conditions, which has the advantages of uniform lignin depolymerization, fast dissolution rate and low degree of carbohydrate destruction. Chlorine dioxide is subsequently used to selectively remove residual lignin in bamboo tissue, which has the characteristics of mild reaction and efficient removal, and can retain the complete structure of bamboo. Finally, mechanical stress is used to carry out in-situ dehydration and compression deformation densification treatment of delignified bamboo boards. By adjusting the internal pore structure of bamboo, the light transmittance and haze of transparent bamboo are regulated, and internal structural defects are reduced through densification, and the fiber bonding strength is enhanced, thereby obtaining transparent bamboo with high strength and toughness and adjustable light and thermal properties.
[0024] The transparent bamboo material prepared by this patented method can not only be used for windows and skylights of buildings, but also for interior decoration, indoor partitions, etc. It can effectively adjust the transmittance of solar radiation, reduce indoor temperature fluctuations, and reduce the energy consumption of air conditioning and lighting, thereby making greater contributions to building energy conservation and sustainable development.
[0025] Compared with the existing bamboo delignification process under normal pressure, the present invention has the following significant advantages: ① The high temperature and high pressure reaction conditions are selected, the penetration rate of the reagent solution in the bamboo tissue is accelerated, and the horizontal, vertical and radial penetration rates inside the flattened bamboo board are more uniform and efficient; ② The alkaline sodium sulfite anthraquinone methanol mixed system is selected as the bamboo delignification reagent, the catalytic effect of anthraquinone, the solubilizing effect of sodium sulfite and methanol can improve the depolymerization and dissolution efficiency of lignin, maintain the integrity of the bamboo board structure and the high degree of polymerization of cellulose; at the same time, by providing hydroxide ions (OH - ), destroying the hydrogen bonds between cellulose, hemicellulose and lignin components, reducing the strength and rigidity of the cell wall, and causing the cells to soften and swell; ③ Selecting highly oxidizing and highly selective chlorine dioxide to remove residual lignin, the reaction conditions are mild and there is less damage to cellulose and hemicellulose.
[0026] Compared with the existing transparent bamboo molding process, the present invention has the following significant advantages: ① The molding process is simple, the processing temperature is low, and the energy consumption is low, and it is an efficient and energy-saving preparation method; ② The micro-nano structure inside the bamboo is regulated by the densification process, the fiber bonding strength is improved, and the structural defects inside the bamboo are reduced, and the mechanical properties of the transparent bamboo are improved to 2-3 times that of natural bamboo; ③ The pore structure in the transparent bamboo is regulated by the densification process, and then the light transmittance, haze and thermal conductivity of the transparent bamboo are regulated; ④ No other polymer impregnation filling is introduced, the processing is simple, the cost is lower, and it can be naturally degraded at the end of its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1 The present invention is a production flow chart of a transparent bamboo building material with high strength, high toughness and adjustable light and heat properties;
[0029] Figure 2 The actual photographs and microstructure scanning electron microscope images of (a) the initial bamboo board, (b) the fully delignified bamboo board and (c) the transparent bamboo material in Example 1 of the present invention;
[0030] Figure 3 (a) a physical photograph and (b) a light transmittance curve diagram of the large-sized initial bamboo board and the transparent bamboo material in Example 2 of the present invention;
[0031] Figure 4 The tensile properties of the large-sized initial bamboo board and the transparent bamboo material in Examples 5 and 6 of the present invention;
[0032] Figure 5 The actual photographs and transmittance and haze curves of the large-sized initial bamboo board and transparent bamboo material in Examples 5 and 6 of the present invention are shown;
[0033] Figure 6 A schematic diagram of light path scattering of the transparent bamboo material in Example 1 of the present invention and a photo of actual light scattering;
[0034] Figure 7 The transparent bamboo material with adjustable light and heat properties is prepared by spraying the surface with polylactic acid solution and nano-vanadium dioxide particles in Example 2 of the present invention. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] like Figure 1 This embodiment provides a method for preparing a transparent bamboo building material with high strength, high toughness and adjustable light and heat properties, comprising the following steps:
[0038] S1. Take a 60 cm long, 20 cm wide, and 0.2 cm thick flattened bamboo board as the initial raw material, measure 5 L of alkaline sodium sulfite anthraquinone methanol mixed solution (the mass ratio of sodium hydroxide, sodium sulfite, methanol, anthraquinone and distilled water is 0.05:0.1:0.2:0.001:1), transfer them together into a high-pressure reactor, set the delignification reaction temperature to 160 ° C, and the reaction time to 1 h;
[0039] S2. After washing the flattened bamboo board with a large amount of delignification in S1 with clean water, transfer it to 10L 8% chlorine dioxide solution to continue removing residual lignin, set the reaction temperature to 50°C, and the reaction time to 2h;
[0040] S3. The fully delignified bamboo flattened board in S2 is washed with clean water, covered with nylon blanket cloth, and transferred to a constant temperature hot press, with a unit pressure set to 0.1 MPa / m 2 , temperature is 25℃, time is 0.1h, and transparent bamboo building materials with high strength, high toughness and adjustable light and heat properties can be produced. Figure 2 The following are the actual photos and microstructure scanning electron microscope images of (a) the initial bamboo board, (b) the fully delignified bamboo board and (c) the transparent bamboo in Example 1 of the present invention. As can be seen from the figure, by pre-treatment with alkaline sodium sulfite anthraquinone methanol reagent under high temperature and high pressure conditions, the structure of the flattened bamboo becomes fluffy, the spacing between the cell wall layers increases, and the lignin is quickly and evenly dissolved. After the residual lignin is directional removed by chlorine dioxide solution, the fully delignified bamboo board is white, indicating that there is no lignin residue and the structure is still intact. After pressure densification treatment, the thickness of the bamboo board is reduced and the internal pore structure is reduced.
[0041] Figure 6 The figure is a schematic diagram of light path scattering of the transparent bamboo material and a photo of actual light scattering in Example 1 of the present invention. As can be seen from the figure, the internal structure of the transparent bamboo material has orientation, and when strong light is irradiated, obvious scattering will occur inside the transparent bamboo material, weakening the light intensity and increasing the refraction path and area of the light, thereby improving the lighting.
[0042] Example 2
[0043] like Figure 1 This embodiment provides a method for preparing a transparent bamboo building material with high strength, high toughness and adjustable light and heat properties, comprising the following steps:
[0044] S1. Take a 60 cm long, 30 cm wide, and 0.4 cm thick flattened bamboo board as the initial raw material, measure 8 L of alkaline sodium sulfite anthraquinone methanol mixed solution (the mass ratio of potassium hydroxide, sodium sulfite, methanol, anthraquinone and distilled water is 0.1:0.1:0.2:0.002:1), transfer them together to a high-pressure reactor, set the delignification reaction temperature to 170 ° C, and the reaction time to 2 h;
[0045] S2. After washing the flattened bamboo board with a large amount of delignification in S1 with clean water, transfer it to 12L 10% chlorine dioxide solution to continue removing residual lignin, set the reaction temperature to 60°C, and the reaction time to 3h;
[0046] S3. The fully delignified bamboo flattened board in S2 is washed with clean water, covered with polypropylene blanket cloth, and transferred to a constant temperature hot press, with a unit pressure set at 0.2MPa / m 2 , the temperature is 35℃, the time is 2h, and a transparent bamboo building material with high strength, high toughness, and adjustable light and heat properties can be produced; Figure 3 (a) is a real photo and (b) is a light transmittance curve of the large-sized initial bamboo board and the transparent bamboo in Example 2 of the present invention. As can be seen from the figure, the natural bamboo board is opaque in the visible light range, while the transparent bamboo treated by two-step delignification and densification has good light transmittance in the visible light range;
[0047] The surface of the transparent bamboo board is coated with a 5wt% polylactic acid solution, and the coating thickness is controlled at 50-100 μm. Figure 7 The transparent bamboo material with adjustable light and heat properties is prepared by spraying the surface with polylactic acid solution and nano vanadium dioxide particles in Example 2 of the present invention. As can be seen from the figure, the ultra-thin coating formed by the polylactic acid solution and nano vanadium dioxide particles on the surface of the transparent bamboo material does not significantly reduce the optical transparency of the transparent bamboo material, but can effectively improve the surface hydrophobicity of the transparent bamboo material.
[0048] Example 3
[0049] like Figure 1 This embodiment provides a method for preparing a transparent bamboo building material with high strength, high toughness and adjustable light and heat properties, comprising the following steps:
[0050] S1. Take a flattened bamboo board with a length of 80 cm, a width of 40 cm, and a thickness of 0.5 cm as the initial raw material, measure 12L of an alkaline sodium sulfite anthraquinone methanol mixed solution (the mass ratio of lithium hydroxide, sodium sulfite, methanol, anthraquinone and distilled water is 0.1:0.2:0.2:0.003:1), transfer them together to a high-pressure reactor, set the delignification reaction temperature to 180 ° C, and the reaction time to 4h;
[0051] S2. After washing the flattened bamboo board with a large amount of delignification in S1 with clean water, transfer it to 15L15% chlorine dioxide solution to continue removing residual lignin, set the reaction temperature to 70°C, and the reaction time to 6h;
[0052] S3. The fully delignified bamboo flattened board in S2 is washed with clean water, covered with polyester blanket cloth, and transferred to a constant temperature hot press, with a unit pressure set at 1 MPa / m 2 , the temperature is 35℃, the time is 6h, and a transparent bamboo building material with high strength, high toughness, and adjustable light and heat properties can be produced;
[0053] The surface of the transparent bamboo board is coated with a 5wt% alcohol-soluble nylon solution, and the coating thickness is controlled at 50-100 μm.
[0054] Example 4
[0055] like Figure 1 This embodiment provides a method for preparing a transparent bamboo building material with high strength, high toughness and adjustable light and heat properties, comprising the following steps:
[0056] S1. Take a 100 cm long, 60 cm wide, 1 cm thick giant dragon bamboo flattened board as the initial raw material, measure 20L of alkaline sodium sulfite anthraquinone methanol mixed solution (the mass ratio of sodium hydroxide, sodium sulfite, methanol, anthraquinone and distilled water is 0.1:0.2:0.2:0.005:1), transfer them together to a high-pressure reactor, set the delignification reaction temperature to 180 ° C, and the reaction time to 6h;
[0057] S2. After the large amount of delignified giant dragon bamboo flattened board in S1 is washed with water, it is transferred to 20L15% chlorine dioxide solution to continue to remove residual lignin, and the reaction temperature is set to 80°C and the reaction time is 8h;
[0058] S3. After the fully delignified giant dragon bamboo flattened board in S2 is washed with clean water, it is covered with cotton yarn blanket cloth and transferred to a constant temperature hot press, and the unit pressure is set to 5MPa / m 2 , the temperature is 40℃, the time is 24h, and a transparent bamboo building material with high strength, high toughness, and adjustable light and heat properties can be produced;
[0059] The surface of the transparent bamboo board is coated with a 5wt% paraffin solution, and the coating thickness is controlled at 50-100 μm.
[0060] Example 5
[0061] like Figure 1 This embodiment provides a method for preparing a transparent bamboo building material with high strength, high toughness and adjustable light and heat properties, comprising the following steps:
[0062] S1. Take a 60 cm long, 20 cm wide, and 0.4 cm thick flattened bamboo board as the initial raw material, measure 8 L of alkaline sodium sulfite anthraquinone methanol mixed solution (the mass ratio of sodium hydroxide, sodium sulfite, methanol, anthraquinone and distilled water is 0.1:0.2:0.2:0.005:1), transfer them together into a high-pressure reactor, set the delignification reaction temperature to 160 ° C, and the reaction time to 1 h;
[0063] S2. After washing the flattened bamboo board with a large amount of delignification in S1 with clean water, transfer it to 10L 10% chlorine dioxide solution to continue removing residual lignin, set the reaction temperature to 60°C, and the reaction time to 2h;
[0064] S3. After washing the fully delignified bamboo flattened board in S2 with clean water, stack them in parallel in a molding mold, cover them with nylon blanket cloth, and transfer them to a constant temperature hot press, setting the unit pressure to 0.5MPa / m 2 , temperature is 35℃, time is 2h, it is possible to produce transparent bamboo building materials with high strength and toughness, adjustable light and heat properties, and expandable width and thickness.
[0065] Example 6
[0066] like Figure 1 This embodiment provides a method for preparing a transparent bamboo building material with high strength, high toughness and adjustable light and heat properties, comprising the following steps:
[0067] S1. Take a 60 cm long, 20 cm wide, and 0.4 cm thick flattened bamboo board as the initial raw material, measure 8 L of alkaline sodium sulfite anthraquinone methanol mixed solution (the mass ratio of sodium hydroxide, sodium sulfite, methanol, anthraquinone and distilled water is 0.1:0.2:0.2:0.005:1), transfer them together into a high-pressure reactor, set the delignification reaction temperature to 160 ° C, and the reaction time to 1 h;
[0068] S2. After washing the flattened bamboo board with a large amount of delignification in S1 with clean water, transfer it to 10L 10% chlorine dioxide solution to continue removing residual lignin, set the reaction temperature to 60°C, and the reaction time to 2h;
[0069] S3. After washing the fully delignified bamboo flattened board in S2 with clean water, the board is stacked in a staggered manner at a certain angle in a forming mold (the paving angle is 1-90°), and then covered with nylon blanket cloth and transferred to a constant temperature hot press, and the unit pressure is set to 0.5MPa / m 2 , temperature is 35℃, time is 2h, it is possible to produce transparent bamboo building materials with high strength and toughness, adjustable light and heat properties, and expandable width and thickness.
[0070] Figure 4The tensile properties of the large-sized initial bamboo board and the transparent bamboo material in Examples 5 and 6 of the present invention; Figure 5 The following are the actual photos and transmittance and haze curves of the initial bamboo board and transparent bamboo material of large size in Examples 5 and 6 of the present invention. It can be seen from the figure that when the delignified bamboo board is stacked in parallel in the same direction and densified into a transparent bamboo material of larger size, its optical transparency does not decrease significantly with the increase of thickness, and the haze does not increase significantly; the tensile strength is higher along the bamboo growth direction and lower perpendicular to the bamboo growth direction, and the mechanical strength difference is significant. When the delignified bamboo board is cross-stacked in the vertical direction and densified into a transparent bamboo material of larger size, its optical transparency decreases with the increase of thickness, and the haze increases significantly; the tensile strength along the bamboo growth direction and the vertical growth direction are approximately equal, and the mechanical strength is more uniform.
[0071] Comparative Example 1
[0072] A method for preparing a transparent bamboo material, comprising the following steps:
[0073] Take a 3-year-old bamboo, cut it into 0.6 mm thin bamboo slices, soak it in peracetic acid solution, heat it to 55°C for normal pressure delignification treatment for 8 hours, wash it with clean water, use ethanol, propanol and other solvents to replace the water in the bamboo slices, then transfer it to epoxy resin for vacuum impregnation for 24 hours, place it in an oven at 55°C for curing for 8 hours, and transparent bamboo can be obtained.
[0074] Comparative Example 2
[0075] A method for preparing a transparent bamboo material, comprising the following steps:
[0076] Take a bamboo, cut a 1.5 mm bamboo piece along the surface, place it in a sodium hypochlorite solution, heat it to 60°C and perform delignification treatment at normal pressure for 8 hours, wash it with clean water, use acetone to replace the solvent, then transfer it to polymethyl methacrylate for vacuum impregnation for 24 hours, place it in an oven at 60°C for curing for 8 hours, and a transparent bamboo material can be obtained. Test Example 1
[0077] The mechanical properties of the transparent bamboo materials with high strength and toughness, adjustable transparency and haze, and natural degradation prepared in Examples 1-6 and the transparent bamboo materials prepared in Comparative Examples 1 and 2 are shown in Table 1:
[0078] Table 1 Mechanical properties of transparent bamboo prepared by different processes
[0079]
[0080]
[0081] After testing, the tensile strength and bending strength of the flattened bamboo board in Example 1 are 220MPa and 150MPa respectively. Comparing the mechanical properties of the transparent bamboo in Examples 1-4 in Table 1, it can be found that the transparent bamboo prepared by the present invention has the characteristics of high tensile strength and bending strength, which can reach up to four times that of natural bamboo. This is because after removing lignin, the surface area of cellulose inside the bamboo increases, the number of hydroxyl groups increases, resulting in an increase in hydrogen bond density, which enhances the hydrogen bonding between fibers and reduces the number of defects inside the material, thereby significantly improving the mechanical properties of the transparent bamboo. The large-sized transparent bamboo prepared by parallel stacking in Example 5 has no significant difference in mechanical properties from Implementation Case 4, indicating that this patent provides a method for effectively expanding the width and thickness of transparent bamboo. The transparent bamboo prepared by staggered stacking in Example 6 has a stacked alternating structure, which can adjust stress distribution, stress transfer and microcrack expansion path, and has good mechanical properties in all directions. In Comparative Examples 1 and 2, the transparent bamboo material formed by resin impregnation has a downward trend in mechanical properties due to the polarity difference between bamboo cells and resin molecules and interface separation.
[0082] Test Example 2
[0083] The optical and thermal properties of the transparent bamboo materials with high strength and toughness, adjustable transparency and haze, and natural degradation prepared in Examples 1-6 and the transparent bamboo materials prepared in Comparative Examples 1 and 2 are shown in Table 2:
[0084] Table 2 Transparency, haze and thermal conductivity of transparent bamboo prepared by different processes
[0085]
[0086]
[0087] As can be seen from Table 2, the transparency, haze and thermal conductivity of the transparent bamboo material prepared by the present invention are related to the density. As the density of the transparent bamboo material gradually increases, its transparency increases, and the haze and thermal conductivity gradually decrease. This is because the light-absorbing substances of the bamboo material are eliminated by directional delignification, and the compression deformation densification treatment reduces the pore structure and weakens the light scattering, thereby achieving the regulation of optical properties and can be used for lighting management. At the same time, due to the inherent low thermal conductivity of cellulose, the overall thermal conductivity of the transparent bamboo material prepared by the present invention is still relatively low, and it has good thermal insulation performance. The present invention can achieve dual regulation of the light and heat properties of bamboo.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a transparent bamboo building material with high strength, high toughness and adjustable light and heat properties, characterized in that: (1) Flattened bamboo board is used as raw material, and a mixed reagent of alkaline sodium sulfite anthraquinone methanol is selected as a medium for softening and swelling bamboo tissue and depolymerizing and dissolving lignin, and the bamboo board is placed in a high-pressure reactor for high-temperature treatment and then washed with clean water; (2) transferring the bamboo board treated in step (1) to a chlorine dioxide solution for treatment and washing; (3) The bamboo board treated in step (2) is transferred to a mold of a constant temperature pressure molding device, and a transparent bamboo board is obtained by low temperature pressing.
2. The preparation method according to claim 1, characterized in that: The flattened bamboo board in step (1) is derived from three to five-year-old moso bamboo, ci bamboo or giant dragon bamboo, and the density of the flattened bamboo board is 0.5-0.8 g / cm 3 .
3. The preparation method according to claim 1, characterized in that: The initial cellulose content in the flattened bamboo board in step (1) is 30%-35%, the initial degree of polymerization DP value of cellulose is 1500-2500, the initial hemicellulose content is 20%-25%, and the initial lignin content is 21%-35%.
4. The preparation method according to claim 1, characterized in that: In the alkaline sodium sulfite anthraquinone methanol mixed reagent in step (1), the mass ratio of alkali, sodium sulfite, methanol, anthraquinone and distilled water is 0.01-0.1:0.1-0.2:0.1-0.2:0.001-0.005:1; the alkali is selected from at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide; the mass ratio of the flattened bamboo material to the alkaline sodium sulfite anthraquinone methanol mixed reagent is 1:5-10.
5. The preparation method according to claim 1, characterized in that: The reaction temperature of the high temperature treatment in step (1) is 120-180° C., the pressure value is 0.15-1.2 MPa, and the treatment time is 0.5-6 h.
6. The preparation method according to claim 1, characterized in that: The effective chlorine content of the chlorine dioxide solution in step (2) is 8%-20%, the mass ratio of the bamboo board treated in step (1) to the chlorine dioxide solution is 1:10-20, the treatment temperature is 40-90°C, and the treatment time is 0.5-12h.
7. The preparation method according to claim 1, characterized in that: The lignin mass of the bamboo board treated in step (2) is reduced to less than 0.5%, and the degree of polymerization DP value of cellulose is 980-1400.
8. The preparation method according to claim 1, characterized in that: The mechanical pressure molding equipment in step (3) refers to a constant temperature hot press or a flat vulcanizer, the molding mold is a flat metal plate or metal frame, and the unit pressure is 0.1-10MPa / m 2 The processing temperature of the low-temperature pressing treatment is 25-40°C, and the pressure treatment time is 0.1-24h.
9. The preparation method according to claim 1, characterized in that: In step (3), during the low-temperature pressing process, a blanket made of nylon, polypropylene, polyester or cotton yarn is selected to cover the delignified bamboo board for buffering and water absorption and dehydration.
10. A transparent bamboo building material with high strength, high toughness and adjustable light and heat properties, prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The density of the transparent bamboo building material is 1.0-1.5 g / cm 3 , the moisture content is 5%-10%, the optical transmittance and haze range are 40%-90% and 20%-80% respectively, and the thermal conductivity is 0.2-0.6W / (m . K), tensile strength of 500-1000MPa, and flexural strength of 300-700MPa.
Citation Information
Patent Citations
A method for preparing transparent bamboo and the resulting transparent bamboo.
CN110978183B
A large-format transparent wood or bamboo material and its preparation method
CN113664938B
Preparation method of high-strength flexible transparent bamboo
CN114851323B
Transparent bamboo oriented strand board and preparation method thereof
CN117124426A